Clinical evaluation of dental alignment and leveling with three different types of orthodontic wires - Gravina,Marco Abdo (2013)
INTRODUCTION: A wide variety of orthodontic wires made of different alloys is available to be used in orthodontic practice and may produce different clinical responses during tooth movement. OBJECTIVE: This research evaluated the alignment and leveling of lower dental arches after the use of three types of orthodontic wires. METHODS: A sample of 36 patients was randomly divided into 3 groups: stainless steel, multistranded steel and superelastic nickel-titanium, according to the first leveling arches used. In order to observe differences in tooth position and axial inclination of the lower incisors, all patients had lateral cephalometric radiographs taken before the insertion of the first arches and 2 months later. The irregularity index and the curve of Spee were measured, compared between groups and considered influential on the proclination of incisors during the initial phase of alignment and leveling. The Reflex microscope was used to measure the irregularity index, whereas the ANOVA analysis of variance was used to verify differences between groups with regard to the degree of dental alignment and leveling. RESULTS: There were significant differences between groups only at T2 for the irregularity index. CONCLUSION: The NiTi and multistranded steel wires showed greater aligning capacity when compared with stainless steel wires.